Fortifying plants with the essential amino acids lysine and methionine to improve nutritional quality. Issue 2 (27th November 2012) - Galili, Gad; Amir, Rachel
Summary Humans, as well as farm animals, cannot synthesize a number of essential amino acids, which are critical for their survival. Hence, these organisms must obtain these essential amino acids from their diets. Cereal and legume crops, which represent the major food and feed sources for humans and livestock worldwide, possess limiting levels of some of these essential amino acids, particularly Lys and Met. Extensive efforts were made to fortify crop plants with these essential amino acids using traditional breeding and mutagenesis. However, aside from some results obtained with maize, none of these approaches was successful. Therefore, additional efforts using genetic engineering approaches concentrated on increasing the synthesis and reducing the catabolism of these essential amino acids and also on the expression of recombinant proteins enriched in them. In the present review, we discuss the basic biological aspects associated with the synthesis and accumulation of these amino acids in plants and also describe recent developments associated with the fortification of crop plants with essential amino acids by genetic engineering approaches.